The how I think questionnaire: assessing its psychometric properties in Bangladeshi culture - Karim, A. K M R; Begum, Taslima (© 2016 Elsevier, 2016)
This article was published in the Asian Journal of Psychiatry [© 2016 Elsevier Ltd.] and the definite version is available at : http://doi.org/10.1016/j.ajp.2016.02.004. The Journal's website is at: http://www.asianjournalofpsychiatry.com/article/S1876-2018(16)30059-4/abstract